Penguatan Ekosistem Pesisir: Monitoring dan Pembelajaran Pembangunan Alat Pemecah Ombak (APO) di Kota Semarang - Reny Yesiana; Itsna Yuni Hidayati; Gunawan Wicaksono (Department of Urban and Regional Planning, Diponegoro University, 2016)
Climate change has been one of the major causes of environmental damage which needs to be anticipated early. In Indonesia, particularly in Semarang City, it has destroyed ponds and mangrove forests through erosion and sea level rise processes. The significant impact of climate change is exacerbated by the lack of public knowledge related to its threat, which in turn affects to the decrease in farmers’ income. This situation encouraged the Mercy Corps Indonesia in cooperation with the Government of Semarang Municipality and the Bintari Foundation to develop activities for strengthening the coastal area protection through the development of seawalls under the program named